(untitled) (JURNAL PROTEKSI KESEHATAN, 2020)
Abstract Cervical cancer is one of malignant neoplasms and number one cancer killer of women in Indonesia. The aim of this research is to Know the Correlation Knowledge Women of Childbearing Age (WCA) With Early Detection of Cervical Cancer in Tanah Datar Village Working Area of Puskesmas Pekan Heran Indragiri Hulu Regency. The research design used descriptive correlation with approach cross sectional. The sampling technique used is purposive sampling and random sampling with the number of 227 respondents. The processing data using univariate and bivariate analysis with Chisquare test. The results obtained were the of WCA who had enough knowledge about cervical cancer as many as 99 respondents (43,6%) and early detection of cervical cancer with method IVA test by WUS majority did not early detection as much as 174 respondents (76,7%). Chi-Square statistical test results obtained that the correlation knowledge with early detection of cervical cancer is p value 0,00 < 0.05. Conclusion: There is a Correlation between Knowledge Women of Childbearing Age (WCA) With Early Detection of Cervical Cancer in Tanah Datar Village Working Area of Puskesmas Pekan Heran Indragiri Hulu Regency.